Mg/Ca ratios in the planktonic foraminifer Neogloboquadrina pachyderma (sinistral) from plankton tows in the Ross Sea and the Pacific sector of the Southern Ocean (Antarctica) : comparison of different methodological approaches - C. Bergami; L. Capotondi; M. Sprovieri; L. Langone; F. Giglio; M. Ravaioli; M. Tiepolo (Chemistry and Ecology, 2008)
Mg/Ca ratios in living specimens of the planktonic foraminifer Neogloboquadrina pachyderma (sin.) have been investigated using Laser Ablation Inductively Coupled Plasma Mass Spectrometry (LA-ICP-MS) and ultracleaning procedures on 'bulk' foraminifera followed by Inductively Coupled Plasma Mass Spectrometry (ICP-MS) and Inductively Coupled Plasma Atomic Emission Spectrophotometry (ICP-AES) analysis. Plankton tows were taken in the upper 250 m of the water column at different sites in the Ross Sea and at the Polar Front of the Pacific Ocean during 6 austral summers. We found high values of Mg/Ca ratios in N. pachyderma (s.) not previously reported in the literature. Our data suggest that at least two factors influence the results: (1) the presence of some protoplasm in the test of living specimens, which seems to control the actual Mg concentration and (2) the morphotype of the analysed specimens in term of test thickness.